PENGARUH KOMPETENSI, SPI DAN SAP TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PALI - Hilaria Prima Andika Putri Sopiyan AR Periansya (JURNAL RISET TERAPAN AKUNTANSI, 2019)
This research was conducted with the aim to know the influence of Competencies of Human Resources, SPI, and SAP on The Quality of Financial Statements of The Pali District Government. The population in question is all employees working in OPD Pali District. The sample used is as much as 117 respondents by using purposive sampling method. The data analysis technique used is multiple linear regression with the help of the data process through SPSS version 22. The result of this study shows that R2 is 37,8%. The result of this study show that Competencies of Human Resources does not affect the Quality of Financial Statements, SPI has a positive and significant effect on the Quality of Financial Statements, and SAP has a positive and significant effect on the Quality of Financial Statements. Simultaneously the independent variables together have an influence on the Quality of Financial Statements.